Surirella arctica comb. et stat. nov. (Bacillariophyta)—a rare arctic diatom - Veselá, Jana; Potapova, Marina (Phytotaxa, 2014)
Surirella terryi var. arctica has been described more than 50 years ago from northern Alaska. Since then, it has not been reported in the scientific literature except for a single record. We studied in detail the holotype slide and material of S. terryi var. arctica and several other samples from northern Alaska, and concluded that S. terryi var. arctica differs from the nominate variety and should be placed in a separate species. Surirella arctica comb. et stat. nov. is presented here including a detailed morphological description and light and scanning electron micrographs. Surirella arctica can be easily recognized due to the internally thickened median area and transverse costae, together forming a craticula-like structure on the interior valve surface. This feature is well visible in the light microscope and helps discriminating S. arctica from other Surirella species similar in valve shape, size and other morphological characters. These taxa include S. angusta, S. heardensis and an unknown species from Siberia and Mongolia. The presence of S. arctica has been confirmed to date only from the northern Alaska and likely from the high Arctic in Canada.